2022
DOI: 10.1186/s12920-022-01404-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered DNA methylation of CYP2E1 gene in schizophrenia patients with tardive dyskinesia

Abstract: Background About 20–30% of patients with schizophrenia develop tardive dyskinesia (TD). Oxidative stress is one potential causes of TD. CYP2E1 is considered as an oxidative stress-related gene, however, no study has been reported on the DNA methylation levels of the CYP2E1 in schizophrenia or TD. Methods A total of 35 schizophrenia patients with TD, 35 schizophrenia patients without TD (NTD), and 35 health controls (HCs) were collected in Beijing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…CYP2E1 enzyme expression is differently influenced by epigenetic variation such as DNA methylation [ 38 ]. DNA methylation levels in the promoter of the CYP2E1 gene have been associated with SCZ and tardive dyskinesia [ 39 ]. In fact, a Chinese case–control study revealed that two CYP2E1 SNPs were associated with SCZ [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…CYP2E1 enzyme expression is differently influenced by epigenetic variation such as DNA methylation [ 38 ]. DNA methylation levels in the promoter of the CYP2E1 gene have been associated with SCZ and tardive dyskinesia [ 39 ]. In fact, a Chinese case–control study revealed that two CYP2E1 SNPs were associated with SCZ [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CYP2E1 is involved in the occurrence and development of neurological diseases. It was found that the low methylation level of CYP2E1 may be related to the underlying mechanism of schizophrenia [ 63 ]. Evaluation of candidate genes by nitrite phosphosequencing in cortical tissue of patients with Parkinson’s disease revealed hypomethylation of CYP2E1 [ 64 ].…”
Section: Dna Methylation and Alcohol Abusementioning
confidence: 99%
“…12,14 Current pyrosequencing technology, applicable to the highthroughput quantification of DNA modifications, is a strong tool for exploring biomarkers of various diseases. 15,16 This method enables the identification of alterations in the methylation status of DNA in the peripheral blood of patients with schizophrenia, 17,18 major depressive disorder (MDD), 19 and bipolar disorder. 20 The methylation levels of the brain-derived neurotrophic factor (BDNF) promoter, measured in the peripheral blood by pyrosequencing, increased in patients with schizophrenia 17 and decreased in those with MDD.…”
Section: Introductionmentioning
confidence: 99%